IMPACT OF PHYSICAL AND ERGONOMIC HAZARDS ON WORKERS’ HEALTH IN MEDIUM-SCALE FACTORIES IN NNEWI-NORTH L.G.A., ANAMBRA STATE, NIGERIA - Ihekwoaba Ebelechukwu Nwaoma; Okoronkwo Wisdom Amarachukwu; Nwachukwu Mathew Chinwemadu; Nwankwo Chidiebere Joy; Onyenekwe Amala Joy (GSC Advanced Research and Reviews, 2026)
Occupational environments in rapidly industrializing settings expose workers to significant physical and ergonomic risks. This study aimed to evaluate the exposure and health impacts of physical and ergonomic hazards among factory workers in Nnewi-North Local Government Area (L.G.A.), Anambra State, Nigeria. Utilizing a descriptive cross-sectional design, structured self-administered questionnaires were gathered from n = 272 respondents across three medium-scale factories (A, B, and C) alongside qualitative interviews and sound-level measurements. Descriptive statistics and Chi-square tests of independence were utilized for data analysis. The sample mean age was 39.10 ± 12.87 years, with 61.4% male respondents and 40.1% possessing over 10 years of work experience. Environmental sound level monitoring recorded the highest average noise in Factory C (85.7 dB). Dominant reported physical exposures included noise (87.1%), slips/trips/falls (86.4%), and extreme temperatures (83.1%), while work stress (78.3%) and awkward postures (52.6%) constituted the principal ergonomic hazards. Prevailing health outcomes were skin irritation (74.9%), musculoskeletal disorders (67.3%), and mechanical cuts (66.9%). Statistical analysis confirmed significant associations between department type and hearing difficulty (X2 = 86.628, p < 0.001), years of experience and hearing difficulty (X2 = 68.928, p < 0.001), as well as department type and musculoskeletal disorders (X2 = 263.240, p < 0.001). Enhanced regulatory oversight, engineering controls, and structured ergonomic interventions are imperative.